2012
DOI: 10.1111/j.1471-4159.2011.07638.x
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II activity regulates neurite outgrowth and guidance in response to chondroitin sulfate proteoglycans

Abstract: Chondroitin sulfate proteoglycans (CSPGs) are major components of the extracellular matrix in the central nervous system (CNS) that inhibit axonal regeneration after CNS injury. Signaling pathways in neurons triggered by CSPGs are still largely unknown. In this study, using well-characterized in vitro assays for neurite outgrowth and neurite guidance, we demonstrate a major role for myosin II in the response of neurons to CSPGs. We found that the phosphorylation of myosin II regulatory light chains is increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…When under injury, F-actin is reported to polymerize at the distal end of injured neuritis and undergoes reorganization and retrograde flow generated by myosin II, the actin-binding motor protein 48, 49. The two isoforms of myosin undertake distinct roles: myosin IIB functions as the molecular motor responsible for neurite outgrowth, while myosin IIA maintains focal contact formation and drives neurite retraction 50-52.…”
Section: Discussionmentioning
confidence: 99%
“…When under injury, F-actin is reported to polymerize at the distal end of injured neuritis and undergoes reorganization and retrograde flow generated by myosin II, the actin-binding motor protein 48, 49. The two isoforms of myosin undertake distinct roles: myosin IIB functions as the molecular motor responsible for neurite outgrowth, while myosin IIA maintains focal contact formation and drives neurite retraction 50-52.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported insights into the mechanisms involved in the regulation of CSPG inhibition, such as myosin II (Yu et al, 2011) and EGFR (Koprivica et al, 2005), along with signaling pathways involving Akt (Fisher et al, 2011) and integrins (Tan et al, 2011). In future studies it will be important to elucidate additional intrinsic properties that may be unique to the insensitivity of NRP-derived neurons to CSPGs.…”
Section: Discussionmentioning
confidence: 99%
“…Myosin II, an ATP-dependent motor protein, appears to mediate CSPG inhibition on neuronal growth (Hur et al, 2011; Yu et al, 2012). CSPGs increase phosphorylation of nonmuscle myosin II regulatory light chains and pharmacological or genetic inhibition of myosin II promotes axon growth on inhibitory substrates including CSPGs.…”
Section: Downstream Signaling Pathways That Convey Growth Inhibitimentioning
confidence: 99%